Community based waste management and its utilization for sustainable environment - Sarkar, SK; Uddin, MK (Bangladesh Journal of Animal Science, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The goal of this study of community based waste management and utilization was to reduce the major negative impact of environment and health hazards created by improperly managed waste mainly focusing on livestock production system of Bangladesh. The waste amounted 4,78,220 kg annually managed by the community contribute to significant role regarding human and livestock health, sanitation, economic as well as environmental aspects. In terms of economic, the Chadkarim community could earn net benefit of Tk. 2,70,146 in 2012 by selling waste by-products, major earnings come from 95,644 kg of organic fertilizer producing amounting Tk. 1,37,546 The global environmental perspective is to reduce livestock-induced, land-based pollution and environmental degradation. One of the major costs of running an agricultural farm can include buying nitrogen in the form of anhydrous ammonia to fertilize crops. But there are other agricultural costs associated with nitrogen, especially when the nitrogen in livestock waste produces pungent and potentially harmful ammonia emissions. To get expected production and to trap optimum socio-economic benefit from livestock rearing, waste must be managed in proper ways through a community based biogas producing approach of waste management to have sustainable environment. During one year community managed 4,78,220 kg degradable waste and produced about 17,216 m3 of biogas and utilized that gas for cooking and electricity generation. The notable benefits come from womens saved time and money. The 200 households at the community in one year have saved 15,881 working days through reduced time required for managing of fuel and cooking purposes. Most of the saved time is being utilized for household tasks and for education of the children. This is one of the greatest contribution to the nation. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> DOI: http://dx.doi.org/10.3329/bjas.v42i2.18506 <span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Bang. J. Anim. Sci. 2013. 42 (2): 165-173